LIPSS‐Sticks: Laser Induced Double Self Organization Enhances the Broadband Light Absorption of TiO2 Nanotube Arrays. Issue 5 (8th March 2021) - Arul, Rakesh; Dong, Junzhe; Simpson, M. Cather; Gao, Wei
Abstract : Sub‐wavelength laser‐induced periodic surface structures (LIPSS) created by ultrashort pulsed laser irradiation on the surface of titanium are used for the first time to template the electrochemical growth of titanium dioxide nanotube arrays, creating a combined structure we term LIPSS‐Sticks. This is an example of a double self‐organized process, as both LIPSS formation and electrochemical anodization involve spontaneous generation of order from initially nonordered precursors. LIPSS‐Sticks have a 2× greater visible to near‐infrared light (400–1400 nm) collection efficiency compared with flat titanium dioxide due to the enhanced light scattering from grating‐like structures. The growth of nanostructures with time is modeled electrostatically to explain the features of a templated anodization process that differ from the usual anodization of flat surfaces. This new templated growth method using two complementary fabrication techniques is general and can also be applied to Cu, W, Fe, and Al oxide surfaces. Abstract : This work uses ultrashort pulsed laser induced periodic surface structures (LIPSS) to template ripples upon which electrochemical anodization is used to grow titanium dioxide nanotubes ("Sticks"). The combined structure, termed LIPSS‐Sticks, effectively traps light from the visible to the near‐infrared (400–1400 nm). The enhanced light extinction is potentially useful for light harvesting applications in photovoltaic devices and photocatalysts.